Composition and distribution of frogs in Crocker Range Park, Sabah, Malaysia, with a description of a new Kalophrynus (Anura, Microhylidae) species - Paul Imbun; Tan Fui Lian; Maklarin Lakim; Luiza Majuakim (Pensoft Publishers, 2013)
We monitored five localities within Crocker Range Park, one of the protected forests administered by Sabah Parks in the Malaysian part of Borneo. The sites selected were at various elevations: lowland sites at 260 m and 499 m a.s.l.; montane sites at 1,216 m, 1,260 m and 1,477 m a.s.l. Forty species were encountered in this study. New discoveries were also found during the course of our three-year period survey (October 2003–October 2006). The discoveries include amongst others, the Sabah endemics of Meristogenys, two new records for Sabah: Sarawakiphrys dringi (Inger, Stuebing and Tan, 1995), and Pelophryne rhopophilia Inger and Stuebing, 1996, as well as a new species, Kalophrynus minutus sp. nov., described herein. These findings provide evidence of many unknown species still waiting to be discovered. These discoveries also add significantly to our understanding of the distribution of frog species in Borneo as a whole, showing that species formerly thought to be very restricted geographically actually have much greater and more extensive distributions within Borneo.